On the first finding of zoned pyrope in the sedimentary cover of the Ukrainian shield - Vyshnevskyi, O.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The first finding of zoned pyrope in terrigenous deposits of Ukraine is described. The grain of ∼0.3×0.4 mm in size is a part of a larger crystal and chemically inhomogeneous. From side to side in them, the FeO content appropriately increases (from 8.6 to 11.6%) and MgO decreases(from 20.6 to 17.8%). Thus, the concentration of other indicator elements (Ti, Ca, Cr) remains unchanged. Based on the analysis of obtained data, it is concluded that its native sources were kimberlites or garnet peridotites of UHPM terranes, and the temperature and the pressure of crystallization were near 800–850 ºC and 2.0 GPa. In respect of the zonality exposed in pyrope, it is most probable that it is a result of its subsolidus alteration in mother rocks at comparatively high temperature and pressure.